Avaliação de políticas públicas de ações afirmativas: a implementação dos NEABI’s - Núcleos de Estudos Afro-brasileiros e Indígenas - no IFCE e as transformações nas relações étnico-raciais - Dias, Érica Fernandes (2020)
The work that is now displayed with the title "Avaliation of public politics of affirmative action: the implementation of the NEABIs - Indigenous and Afrobrazilian studies cores at the IFCE and the transformations in ethnic-racial relationships avaluates the implementation of these cores on the Federal Institute of Education, Science and Knowledge of Ceará, in the period between 2014 and 2019, while considering it`s atributions as expected according to law number 10.639/03, in what concerns to the ethnic-racial relationships. This avaluative proposal is based on the counter hegemonic perspective referenced in the paradigm of the Profound Evaluation in articulation with the Experiential Model of Lejano, in the orientation of making possible a look that extrapolates the simple observing of the fulfillment of the goals and headlines of the public politics, bringing forward social inferences, perceptions and subjectivities of the subjects that elaborates them, insert them and live them. The research utilized of bibliographical data, documentation analysis, and case study, through field work. I prioritized the crossover of two technical instruments: quizzes - to the teachers - and semi-structured interviews - realized with representatives of the pro-rectory of teaching and extension (PROEN and PROEXT), who are key-subjects to the construction of this debate. This study was orientated by structural and foundational, pertinent to the implementation of the NEABIs: evaluation of public politics, ethnic-racial relationships, afrobrazilian and indigenous study cores, institutional racism and afrobrazilian identities. This evaluative research made evident that considerable change has occured in relationship with the approach of ethnic-racial issues, after the start of NEABIs, at IFCE, through actions developed by these cores. There is also the revelation of the insertion of these in other spaces of power, even though in a shy way, as in the example: the dialogue estabilished with the teaching to the inclusion of law number 10.639/03 in the curriculum; the creation of heteroidentification benches; participation, even though contracted, in the pedagogical encounters; growing commitment of the members of the cores and the constant struggle for the promotion of racial equality. But the research has also revealed the existence of the urgency of the need to overcome some situations, like, for example: the division of the responsability that the NEABIs have carried - in a sense that these cores are acting almos like they are alone on what matters to antiracist and reparatory actions inside the context of IFCE; the safeguard of the right of more economical and political support to the iniciatives that seek the strenghtening of the law number 10.639/03; the overcome of stigmas translated daily in bad looks to the african/africanbrazilian cultural elements. NEABIs have seeked to approach, even with limitations, inside the institue, the racism as a central issue to comprehend society and it's complexities in contemporaneity, have contributed to the decolonization of the curriculum and the teaching practices and to the growing appreciation and visibility of identities, of the cultural patrimony and history of black people and african descendents, with the goal of self-affirmation of these historical subjects.